Normativno-pravovì akti Ukraїni : deâkì teoretičnì aspekti - Kosovič, Vìtalìj (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
In this article defined of the normative legal act, selected his basic indication, considered system normative legal acts of Ukraine, paid attention on questions publication and accumulation validity normative legal acts. In this case accent is only on discussion moment.
Keywords: Ukraina; akty normatywno-prawne; teoria prawa